Women Economic Empowerment through the Lens of Financial Inclusion in Pakistan: Analysis of the Moderation Effect of Financial Literacy - Sadiq, Maimoona; Ihsan, Anjum; Hameed Khattak, Amjad (Journal of Business & Tourism, 2023)
This study analyzes how financial literacy influences the linkage between financial inclusion and economic empowerment of women. The study examines the impacts on women entrepreneurs actively working in Pakistan. This study is descriptive, and a quantitative research method is applied. A cross-sectional study design opts to study the variables under a single period and data was collected using structured questionnaires. Using the sampling technique of Bentler & Chou (1987), the research comprised a sample of 120 women entrepreneurs that are active and registered with the Women Chamber of Commerce Pakistan. Results suggested that women’s economic empowerment is significantly and positively affected by financial inclusion. Additionally, a significant impact of financial literacy on women’s economic empowerment has been observed. This study attempts to help policymakers identify barriers that prevent the underserved in society, especially women, from accessing financial products and services. The study also highlights the importance of financial literacy. It will encourage policymakers to introduce financial literacy programs to help individuals, especially women, better manage their finances and make informed decisions, thus fostering more inclusive and sustainable economies.